Checklist of flesh flies of Turkey (Diptera, Sarcophagidae) - Verves, Yury; Barták, Miroslav; Kubík, Štěpán (ZooKeys, 2018)
A checklist of 153 flesh fly species (Diptera, Sarcophagidae) recorded to date from Turkey is presented. Updating the list was necessary due to the numerous recent records. Records are listed according to provinces.
Keywords: Turkey; Sarcophagidae; distribution; checklist